Hypnotic suggestion for the treatment of tinnitus - Walery Zukow; Oleksandr Suvorkin (Nicolaus Copernicus University in Toruń, 2023)
Aim of study. Considering the high spreading of tinnitus in population, the purpose of our research was to study the possibility and expediency of using hypnosuggestive therapy in treatment of tinnitus.        Material and methods. The study included 55 people with tinnitus complaints. We divided three groups of patients depending on the severity of the manifestations, audiometry results, Tinnitus Handicap Inventory (THI) score according to this scale of severity, results of GAD-7 test and the PHQ-9 (Patient Health Questionnaire -9).    Results. In the first group of patients, according to the tinnitus severity scale the score was up to 19 points and was considered as insignificant and mild. The score of the GAD-7 questionnaire was less than 8 points, PHQ-9 - up to 5 points. In the second group the severity of tinnitus was moderate and severe and counted more than 38 points. The GAD-7 questionnaire score was less than 8 points, PHQ-9 - up to 5 points. In the third group, 12 people complained of chronic tinnitus, sleep disturbances, nervousness, and reduced work capacity. The score of tinnitus severity in patients of this group was more than 58 points and was assessed as severe and catastrophic. According to the results of the GAD-7 and PHQ-9 questionnaires, all 12 people were diagnosed with anxiety disorders and depression, two parients even had suicidal thoughts.  In the third group of patients with +++ hypnotability, after ten sessions of individual hypno-suggestive therapy, it was possible to reduce the severity of tinnitus to the third moderate degree in 7 people. 4 patients reported about complete regress of tinnitus.    Conclusions. Tinnitus is a common problem and can negatively affect work, family and social life. It requires the individual approach and involvement of specialists of various profiles in the diagnostic process. The diagnostic algorithm for patients with tinnitus should include questionnaires to estimate the psychosomatic profile. The use of hypno-suggestive therapy can significantly reduce the severity of tinnitus and improve the quality of lives of patients.